Respuesta :

9514 1404 393

Answer:

  c)  x^2 - 9x - 22 = 0

Step-by-step explanation:

Consider the generic case ...

  (x -a)(x -b) = 0 . . . . . . . has solutions x=a, x=b

Multiplying this out gives ...

  x^2 -ax -bx +ab = 0

  x^2 -(a+b)x +ab = 0

This tells you ...

  • the coefficient of x is the opposite of the sum of the roots
  • the constant is the product of the roots

The sum of roots is 11 +(-2) = 9, and the opposite of that is -9. You are looking for an equation with the term -9x. (Choice C matches)

The product of roots is (11)(-2) = -22. You are looking for an equation with a constant of -22. (Choice C matches that, too.)

The equation is ...

  x^2 -9x -22 = 0